Novel surface-acoustic wave transducers - R. C. WOODS (Archives of Acoustics)
The conventional means of launching a Surface Acoustic Wave on a piezoelectric substrate is by using an inter-digital transducer. A modified structure using multilayer deposition, but only a single critical photolithography stage, is proposed in this paper. The potential advantages of this structure include greater ease of manufacture and/or access to higher frequencies. Several variants of the basic principle are possible, and these are analysed using a simple equivalent circuit model. Experimental results for several fabricated devices, including apodised (weighted) transducers, are presented. These results show that the technique is a viable method of launching surface acoustic waves and that the flexibility of the concept should approach that of the conventional type of transducer, with much scope for future development of more advanced versions.